Controlling superconductivity with strong terahertz fields - Hoffmann, Matthias C.; Dienst, Andreas; Kaiser, Stefan; Cavalleri, Andrea; Fausti, Daniele (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
Ultrafast mid-infrared and terahertz pulses open a new avenue to control complex solids by directly accessing their low-energy excitations. Here we discuss recent results in inducing and manipulating superconductivity in cuprate compounds using strong fields. © 2012 OSA.
CRIS-Team Scopus Importer:2022-07-20